2021
DOI: 10.1098/rsos.201785
|View full text |Cite
|
Sign up to set email alerts
|

Ion release from hydroxyapatite and substituted hydroxyapatites in different immersion liquids: in vitro experiments and theoretical modelling study

Abstract: Multi-substituted hydroxyapatites (ms-HAPs) are currently gaining more consideration owing to their multifunctional properties and biomimetic structure, owning thus an enhanced biological potential in orthopaedic and dental applications. In this study, nano-hydroxyapatite (HAP) substituted with multiple cations (Sr 2+ , Mg 2+ and Zn 2+ ) for Ca 2+ and anion ( Si … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 81 publications
(154 reference statements)
12
49
0
Order By: Relevance
“…However, the information on ion release from hydroxyapatite required studying this issue to be sure that all tested llers are safe against probiotic bacteria that are present in the gastrointestinal tract and may be exposed to ions released e.g. in the oral cavity [32].…”
Section: Fillersmentioning
confidence: 99%
“…However, the information on ion release from hydroxyapatite required studying this issue to be sure that all tested llers are safe against probiotic bacteria that are present in the gastrointestinal tract and may be exposed to ions released e.g. in the oral cavity [32].…”
Section: Fillersmentioning
confidence: 99%
“…For example, Andrés et al showed that the degradation rate of Mg substituted HAP in PBS, PBS with lysozyme, and acetate buffer increases with increasing Mg content [18]. The surface of multi-substituted HAP nanoparticles (Mg, Zn, Sr, Si-HAP and Mg, Zn, Si-HAP) was shown to be more susceptible to dissolution in SBF (simulated body fluid) and water due to the lattice strain provoked by the simultaneous multi-substitution of ions in the structure of HAP [19]. However, to date, no data on the changes in the local structure of Mg-substituted HAP during exposure to different media has been published.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, gamma radiation induces defects or free radicals in the material with a different nature and structure, which depend on the composition and the synthesis conditions of the samples. In addition, they can present different behaviour in physiological solutions [19]. Furthermore, due to the importance of the shelf-life of the material for biomedical applications and storage conditions, the accelerated ageing method is used.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the bioactive performance of bioceramic materials was improved by substituting various elements that are essential for bone regeneration, such as Mg, Zn or Si [20][21][22][23][24][25][26], into the HAP lattice, resulting in multi-substituted HAP (ms-HAP) bioceramics. The interest in this substitution originated from the well-established role of these elements in bone regeneration [27,28].…”
Section: Introductionmentioning
confidence: 99%